Ilio-Iliac Arteriovenous Fistula with May-Thurner Syndrome: A Case Report - Tae Hyeon Kim; Jae Woo Yeon; Hyuk Jung Kim; Suk Ki Jang (Journal of the Korean Society of Radiology, 2024)
An ilio-iliac arteriovenous fistula (AVF) is rare. Common factors leading to ilio-iliac AVF include congenital malformations, iatrogeny, and trauma. There is limited documentation in the literature of cases involving ilio-iliac AVF with May-Thurner syndrome. Here, we present a case of an ilio-iliac AVF with May-Thurner syndrome in an 80-year-old male. CT and angiography confirmed extensive ilio-iliac AVF. Successful endovascular procedures for ilio-iliac AVF were performed using several variablesized coils and 1400–2000 μm gelatin particles. After embolization, follow-up abdominopelvic CT revealed an improvement in edema in the left leg.